Transient response to perturbations in flow synthesis of citrate capped gold nanoparticles - Bari, Atul H.; Shukla, Neerja; Gavriilidis, Asterios; Kulkarni, Amol A. (Biochemical Engineering Journal, 2023)
This work reports the transient behavior of continuous flow synthesis of gold nanoparticles (Au NPs) when subjected to perturbations in operating conditions using controlled experiments. The intricacies are captured through a detailed mathematical model. Reversed Turkevich protocol was used for synthesis of Au NPs. The synthesis was first studied in batch mode to investigate the reaction kinetics and reproducibility of the process. The optimal set of operating conditions viz., residence time, flow rate, temperature was then used for flow synthesis in a 2 m, 1/16 & DPRIME;Polytetrafluoroethylene (PTFE) reactor with micromixer. Reactor clogging was avoided by using segmented flow. Inline UV measurement was used for real time monitoring of the process. Transient experiments were performed by abruptly changing the operating conditions. A mathematical model was found to be accurate in predicting the transient behavior of the exit precursor concentration and the particle size for unsteady state synthesis. Even a small change in process variables for short duration was found to disturb the quality of Au NPs for a significantly longer duration. Of the three operating parameters, the effect of temperature variation was seen to have a prolonged effect where the system remained in unsteady state for long time.
Keywords: continuous flow synthesis; gold nanoparticles; Particle size; segmented flow; Unsteady behavior